Al 'Adah Muhakkamah Rules and Their Applications Regarding the Contemporary Era Share Purchase and Sale Agreement - Muhamad Iqbal Akbar; Mohamad Fikri bin Mohd Bakri (Sharia Oikonomia Law Journal, 2024)
The principles of "Al-'Adah Muhakkamah" within Islamic law, particularly its relevance to contemporary financial practices such as share trading. It highlights the significance of customs (al-'adah) as a legitimate source of law in Islamic jurisprudence, allowing for flexibility and adaptability in financial transactions. The study outlines the essential conditions for valid share buying and selling, emphasizing mutual consent, the halal nature of the objects involved, and the avoidance of prohibited elements like usury (riba) and excessive uncertainty (gharar). Utilizing qualitative research methods, literature reviews, and content analysis, the research investigates how these principles are applied in modern contexts, especially through digital platforms. The findings indicate that while the rules of Al-'Adah Muhakkamah provide necessary flexibility to accommodate social and economic developments, there are concerns regarding overly lenient interpretations that may stray from core Islamic principles. The document advocates for a balanced approach that honors traditional Islamic values while addressing contemporary financial practices, ensuring that adaptations remain aligned with Sharia principles. This study serves as a valuable resource for scholars, practitioners, and policymakers in the field of Islamic finance, offering insights into the dynamic interplay between tradition and modernity in financial transactions.